Hubungan antara Intensitas Penggunaan Gadget Terhadap Ketajaman Penglihatan pada Siswa SDN 1 Banda Sakti Kota Lhokseumawe - Mulyati Sri Rahayu; Muhammad Arvin Harwansya; Cut Sidrah Nadira (STIKES Columbia Asia Medan, 2025)
Communication tools in today's era that can be carried anywhere are called gadgets. The use of this modern communication tool occurs as an effort to develop technology in the world. Excessive use of gadgets can trigger eye health disorders that result in computer vision syndrome. The purpose of this study was to determine the relationship between gadget use and visual acuity in students of SDN 1 Banda Sakti, Lhokseumawe City. The cross-sectional approach is the research method used, the measuring instrument used is a snellen chart and a gadget usage questionnaire. The sampling technique used was Stratified random sampling with a total of 152 students as respondents. The results of the analysis using the chi-square test were obtained in the right eye, most respondents with good duration and position of gadget use experienced mild visual acuity disorders while those who were not good mostly experienced moderate visual acuity disorders. For the distance and lighting categories when using gadgets, respondents both experienced moderate visual acuity disorders. For the left eye of respondents with good and bad gadget use, most of them had mild visual acuity disorders. It can be concluded that there is a significant relationship between the duration, position, and distance of gadget use and visual acuity in students of SDN 1 Banda Sakti, Lhokseumawe City.